English for Medical Purposes in Algeria: Challenges and Solutions (مجلة الواحات للبحوث والدراسات, 2023)
Abstract:      As many domains, teaching English to medical doctors has become a necessity as a lingua franca in the age of globalization., in Algeria,  however, where medicine is taught in French, this necessity has taken time to be a reality. Thus, learning experience in this context is challenging because of different difficulties doctors may face with English. A review of EFL and ESP literaturesprovides many approaches to address the issue. These approaches have given sound theoretical and empirical proofs of efficiency worldwide. Content based instruction, as this paper attempts to show, is an instance to adopt in such situation. This conclusion is drawn from both literature and a study in which thirty-five medical specialists in Touggourt, Algeria responded to a questionnaire used as a data collection tool. Keywords: Medicine, Algeria, English Teaching, English for Medical Purposes,Content Based Instruction. ملخص: لقد أصبح تدريس اللغة الإنجليزية للأطباء كباقي التخصصات ضرورة كونها لغة تواصل مشترك زمن العولمة. لكن في الجزائر حيث يدرس الطب باللغة الفرنسية فإن هاته الضرورة أخذت وقتا لتصبح واقعا.لهذا فإن خوض تجربة تعلمية في هذا السياق تعتبر تحديا بالنظر لمختلف الصعوبات التي يواجهها الأطباء مع الإنجليزية. وبتفحص لأدبيات الإنجليزية كلغة أجنبية و لغة لأهداف خاصة نجد مقاربات أعطت أدلة ملموسة لكفاءتها على المستويين النظري و التطبيقي عالميا يمكن أن تمثل حلا للمشكلة. تحاول هذه الورقة أن تبين أن التعليمية القائمةعلى المحتوى  هي نموذج يمكن إعتماده في هاته الحالة. خلاصة مستمدة من الأدبيات وكذا من دراسة شارك فيها خمس وثلاثون طبيبا مختصًا في ولاية تقرت بدولة الجزائر عن طريق الإستبيان  كأداة لجمع البيانات.  كلمات دالة : الطب ، الجزائر ،تدريس الإنجليزية، الإنجليزية لأغراض طبية ، التعليمية القائمة على المحتوى